(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Sinonasal polyposis is a very common presentation among patients attending the Otorhinolaryngology outpatient clinics. Though the overall incidence of patients presenting with clinical symptomatology may not be high, however the chronicity of symptoms causes considerable morbidity to those affected. This in turn warrants either conservative medical treatment or as in most cases, surgical approach for resolution of the symptoms. The current study is aimed at studying the various clinical presentations of patients with sinonasal polyposis, the response following conservative medical treatment, the outcome of the different surgical approaches and the histopathological spectrum of the various sinonasal polyps. Methods: This was a hospital based clinical observational study including a total of 30 patients presenting with sinonasal polyposis over a period of one year. Results: Around 70% of patients had history of allergy and infection as etiological risk factors. Most of the patients presented with nasal obstruction followed by other complaints like discharge, headache, epistaxis and smell disturbance for duration around 3-6months. Initially all patients were treated with conservative medical management. Those patients who did not show symptomatic improvement were taken up for surgery. Any of the three surgical approaches that included FESS (Functional Endoscopic Sinus Surgery), Caldwell Luc or Intranasal Polypectomy were undertaken in 27 patients based on indications. Out of the 27 patients who underwent surgery, 16 patients underwent FESS, of whom 75% improved symptomatically at 2 weeks and 88% improved at 6 weeks of duration. Out of 4 patients who underwent Caldwell Luc surgery, 50% improved at 2 weeks and 75% cases improved at 6 weeks of post-operative period. Out of 7 cases who underwent Intranasal Polypectomy, 43% improved in 2 weeks and 57% improved in 6 weeks post-surgery. On comparison of VAS, maximum improvement was seen in FESS and least improvement in intranasal polypectomy. On histopathological study, maximum patients (55.56 %) had eosinophilic sinonasal polyps followed by inflammatory sinonasal polyps. Conclusion: Surgical management continues to remain as the mainstay of treatment for a case of sinonasal polyposis. Out of all three surgical approaches, best outcome was shown by FESS followed by Caldwell Luc than Intranasal Polypectomy. Least complications were seen in FESS.